Cognition, Relevance and Ideology Formation through Travel Documentaries: A Longitudinal Approach to Audiences - Castaldi Jacopo (Studies in Logic, Grammar and Rhetoric, 2024)
The paper proposes a novel longitudinal approach to the study of the rhetorical effects of media by combining Audience Research (e.g. Schrøder et al., 2003), Social Semiotics (e.g. Kress and van Leeuwen, 1996, 2001; van Leeuwen, 1999; Machin and Mayr, 2012) and Relevance Theory (Sperber and Wilson, 1995). After introducing a more nuanced model of RT’s contextual effect, the paper reports an empirical case study to explicate the methodological approach. Evidence is provided that a specific text can have a long-lasting effect on an audience: a hierarchy of effects and the cognitive circumstances under which this may happen are discussed.